Linguistic knowledge types and past-time inflectional output of Malay users of English - Mohammad Lotfie, Maskanah; Salleh, Nurul Aadilah; Abdul Kadir, Maimunah (International Islamic University Malaysia, 2015)
Acquiring the tense-aspect morphological system of English is challenging to second language learners due to the multifaceted nature of temporal markers. Acquisitional complexities may also be caused by the absence of parallel indicators in the mother tongue and the types of linguistic knowledge that users have. This paper highlights Malay-English differences in temporal markers and reports an investigation on language learners’ production of past-time inflections [-en] and [-ed] and their relationship with linguistic knowledge. Seventy-two Malay English majors who use English as a second language participated in the study. Data were collated using three instruments namely the Grammaticality Judgment Test (GJT), the Metalinguistic Knowledge Test (MKT) and the Written Production Test (WPT). Correlational evidence between explicit and implicit knowledge and target item output was found. Qualitative analysis of written data indicates consistent usage of [-ed] inflection but not [-en]. The findings of the study will enhance theoretical understanding of the role of linguistic knowledge on the development of learners’ inflectional morphology and can encourage sound instructional practices in the classroom.